(untitled) (Brazilian Journal of Behavioral and Cognitive Therapy, 2004)
The present paper has the objective of presenting a discussion about delirium and hallucinations seen here as classes of problem behaviors. Delirium and hallucination are analysed under a natural science point of view, based on the contributions of Skinner’s (1957) theory of verbal behavior and Staats (1996) language theory. Scenes of the movie A Beautiful Mind were used to illustrate the behavioral interpretation of such class of verbal behaviors. The motion picture presents the true story of a man diagnosed as paranoid schizophrenia. Delirium and hallucination are words frequently associated with mentalistic concepts as active explanations of behavior. The behavior is explained by the concept, in a circular way. It is proposed that instead of mental concepts, it is the strange, out of the ordinary behaviors that should become object of study.